Graphene oxide based low cost battery - Gupta, R. K.; Alahmed, Z. A.; Yakuphanoğlu, Fahrettin (Elsevier, 2013)
The electronic devices are shrinking in size which requires high performance small size batteries for power generation. Much effort has been paid to enhance the performance and lower the fabrication cost of the batteries. In this work, we have utilized low cost synthesized graphene oxide for power generation applications. Graphene oxide was synthesized using modified Hummer's method. X-ray diffraction and FT-IR were performed to verify the structure of the synthesized graphene oxide. The current-voltage and power-voltage characteristics confirm that pure graphene oxide could be used for power generation. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Graphene oxide; Spin coating; X-ray diffraction; Battery